Demonstration of Doublecortin Protein, a Neurogenesis Marker, at the Electron Microscopic Level - KAYA, ÖZLEM TUĞÇE; ŞİRVANCI, SERAP (AVES PRESS LTD, 2017)
Objective: Demonstration of newly born neurons in adult brains is an important issue in terms of elucidating neurogenesis. In our study, we aimed to develop an appropriate pre-embedding microwave labeling method for the newly born neuronal marker doublecortin (DCX) protein in the hippocampal dentate gyrus (DG) region. Methods: Brains were obtained from 10-week-old C57BJ/6J male mice by perfusion fixation. Vibratome sections from brain tissues were labeled with an anti-DCX antibody using a pre-embedding microwave method. Sections stained with 3.3'-diaminobenzidine (DAB) were prepared for electron microscopic (EM) analyses using a microwave. After embedding in Epon, thin sections were obtained, observed under an electron microscope, and photographed for morphological assessments. Results: DCX labeling performed using the pre-embedding microwave method was specifically demonstrated at both light and electron microscopic levels. DCX-positive cells were localized at the subgranular zone and granular layer. Electron microscopic observations showed that DCX immunoreactivity was positive at the axons, dendrites, and somata. Conclusion: We demonstrated that the existence of DCX can be determined using the pre-embedding microwave labeling as an immunoelectron method in the DG region. Our study provides a basis for further studies on neurogenesis aiming to show DCX-immunoreactive cells using the pre-embedding DAB labeling method at the electron microscopic level.
Keywords: Neurogenesis; doublecortin; pre-embedding microwave technique; immunoelectron microscopy; CENTRAL-NERVOUS-SYSTEM; ADULT NEUROGENESIS; HIPPOCAMPAL NEUROGENESIS; DENTATE GYRUS; NEURONS; BRAIN; MICROTUBULES; EXPRESSION; CELLS